Izkušnje Slovenije na poti v evroatlantske povezave - Udovič, Boštjan (IB revija (Ljubljana), 2015)
This article presents the development of the national economies of Slovenia and Montenegro as well as the similarities and differences between both. The purpose of this article is to highlight the developments in both countries and to determine whether Slovenia can serve as a good example for Montenegro with regard to Euro-Atlantic integration. The main finding of the article is that the two countries should collaborate in the economic and political sphere because they have similar interests. Slovenia, which has had a great deal of experience in political and economic transition over the last 25 years, is also well versed in adapting to the requirements of Euro-Atlantic integration. This can serve as a productive platform for Montenegro in order to avoid the pitfalls encountered by Slovenia during its accession process.
Keywords: Transition; Tranzicija; Economic crises; Ekonomske krize; Economic crisis (2008); Gospodarska kriza (2008); Slovenia; Slovenija; Črna gora; Montenegro; ekonomska kriza; ekonomsko sodelovanje; mednarodni ekonomski odnosi